2017
DOI: 10.3892/or.2017.6004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FSTL1 on cell proliferation in breast cancer cell line MDA-MB-231 and its brain metastatic variant MDA-MB-231-BR

Abstract: In the past decades, altered Follistatin-like 1 (FSTL1) expression has been documented in a variety of cancers, while its functional roles are poorly understood. Particularly in breast cancer, the expression of FSTL1 and its signaling pathway remain to be determined. In the present study, an elevated FSTL1 expression and a supressed cell proliferation were detected in a specific brain metastatic cell line MDA-MB-231-BR (231-BR), compared with its parental cell line MDA-MB-231. However, this protein was hardly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…FSTL1 inhibits cell proliferation through smad3 in MBA-MD-231 cells, as observed previously [ 27 ]. To explore the function of FSTL1 in vivo , we employed FSTL1 deficient mice.…”
Section: Discussionsupporting
confidence: 83%
“…FSTL1 inhibits cell proliferation through smad3 in MBA-MD-231 cells, as observed previously [ 27 ]. To explore the function of FSTL1 in vivo , we employed FSTL1 deficient mice.…”
Section: Discussionsupporting
confidence: 83%
“…Brown preadipocytes were transfected with lentiviral vector containing shRNA sequences for relevant RNA interference experiments and then subjected to differentiation. The experimental details were shown in our previously study [30]. To overexpress PPARγ2 in brown adipocytes, lentiviruses were produced by transfecting pLVX-PPARγ2 plasmids (a kind gift from Dr. Huang), pSPAX2 and pMD2G (purchased from Addgene) into 293T cells, viral particles accumulated in the supernatant and high-titer viral preparations could be obtained by ultracentrifugation, lentivirus was titrated before transfecting into brown adipocytes with polybrene.…”
Section: Rna Interference and Lentivirus Productionmentioning
confidence: 99%
“…On the other hand, increased expression of FSTL1 compared to healthy control tissue was observed in brain cancer cells [ 18 ], in fibroblasts but not in epithelial cells in colon tumours [ 59 ], in castration-recurrent prostate cancer [ 60 ], in most cases of hepatocellular carcinomas (HCC) [ 61 ], in head and neck squamous cell carcinoma (HNSCC) [ 62 ], and esophageal squamous cell carcinoma (ESCC) [ 63 ]. FSTL1 is higher expressed in metastatic brain tumours compared to primary breast cancer [ 64 ]. FSTL1 is not expressed at a detectable level in normal brain tissue and in diffuse-infiltrating astrocytes of grade II or III gliomas, but is expressed at high levels in grade IV gliomas, referred to as glioblastoma [ 18 ].…”
Section: Cancer and Tumoursmentioning
confidence: 99%
“…Transfection of lung NSCLC cell lines (PC-14 and H446) [ 58 , 67 , 68 ], ovarian, endometrial [ 19 ], NPC [ 22 ], and breast cancer [ 64 ] cell lines with FSTL1 reduces their growth rate via an unknown signaling pathway. Overexpression of FSTL1 in ovarian or endometrial cells was also found to increase the rate of apoptosis via a death receptor-initiated pathway.…”
Section: Cancer and Tumoursmentioning
confidence: 99%